Prosthetic Rehabilitation in the Lower Limb - Bernard O'Keeffe (Indian Journal of Plastic Surgery, 2019)
Lower limb amputations form a considerable number with 5,436,000 Indians having locomotor disability. Most members of this group are young, active earning males. The major cause of amputation is trauma. Hence, this population must be rehabilitated with priority, and best concerted efforts must be made by the medical community. In this article, the authors present available modern technologies in India and share best practices from their experience of treating Indian amputees for the past 20 years. The objective is to demonstrate to the medical community the optimal outcomes that can be achieved and help them make correct decisions on behalf of patients and their families. The article discusses history of prostheses, how to select optimal amputation level, preamputation preparation, determinants of good outcomes, preprosthetic preparation, components of prosthesis, their function and significance, rehabilitation process and guidelines, prescription criteria, and also special considerations such as multiple amputees or children.